Effects of Elastic Taping Application Added on Conventional Rehabilitation Therapy to Improve Shoulder Pain and Upper Extremity Motor Function on Subacute Phase Stroke Patients with Shoulder Subluxation - Bimo Sutomo; Subagyo; Martha Kurnia Kusumawardani (Indonesian Journal of Physical Medicine & Rehabilitation, 2020)
ABSTRACTIntroduction: To determine the effect of adding elastic taping to conventional rehabilitation therapy onthe improvement of shoulder pain and motor function of the upper limbs in patients with subacute strokewith shoulder subluxation.Methods: Research subjects who met the inclusion criteria were recruited from medical rehabilitationclinic in RSUD Dr, Soetomo. The total research subjects were 20 people (10 in treatment group and 10 incontrol group). The parameters were Visual Analoque Scale (VAS) for assessing shoulder pain and FuglMeyer Assessment (FMA) for assessing motor function in the upper limb s.Results: There were significant differences before and after therapy for 3 weeks for VAS (p value = 0.00)in the treatment and control groups, there were significant differences in FMA in the treatment group (pvalue = 0.04), there were no significant difference in FMA in the control group (p value = 0.06). Therewas no significant difference in changes of VAS (p value = 0.23) and FMA (p value = 0.32) between thetreatment and control groups before and after therapy for 3 wee ks.Conclusion: The treatment group and the control group gave the same results on improvement ofshoulder pain and motor function of the upper limbs before and after therapy for 3 weeks. There was animprovement in motor function of the upper limbs in the treatment group and there was no improvementin motor function of the upper limbs in the control group befor e and after therapy for 3 weeks.Keywords: conventional rehabilitation therapy, elastic taping, Fugl Meyer Assessment (FMA),Glenohumeral subluxation (GHS), Hemiplegic shoulder pain (HSP), Visual Analoque Scale (VAS).